Developing BoardWise : A Digital Board Game for Enhancing Elementary Science Education - Ali, Fathan Faqih; Sari, Prima Mutia (Jurnal Paedagogy, 2025)
This study aims to develop and determine the feasibility of a digital board game, "BoardWise," based on Fun Learning principles to enhance the quality of Science Education. Employing a Research and Development (R&D) method, the study progresses through iterative cycles of needs analysis, design, validation, and testing. Data collection involves questionnaires and observations with media experts, material experts, an educator, and fourth-grade students. Data analysis uses descriptive percentages to determine product feasibility. The research results show that the "BoardWise" digital board game is "Very Feasible." The product validation achieves an overall feasibility score of 85.13%, with detailed assessments from a media expert (90.0%), a material expert (83.0%), and an educator (86.0%). Student trials also yield a "Very Feasible" rating with an average score of 81.5%, indicating that the game is highly engaging and practical for classroom use. The study concludes that the "BoardWise" digital board game is a valid, practical, and effective instructional medium. It successfully integrates curriculum content with engaging, customizable game mechanics, fostering an active and enjoyable learning environment that overcomes challenges associated with abstract scientific topics and improves student participation in elementary education.